Experiences and perceptions of the strategy “Today no sanitary circulates” in the context of the Covid-19 pandemic in the city of Pachuca, Hidalgo, México (Revista de Investigaciones Universidad del Quindío, 2021)
The present work allows to identify, through phenomenological qualitative research, the experiences and perceptions that the population of the city of Pachuca, Hidalgo has had about the Social Marketing Strategy “Hoy No Circula Sanitario”, of the Operativo Escudo of the State Government program. This strategy aimed to reduce the mobility of people in the context of the Covid-19 pandemic. In-depth semi-structured interviews were conducted with residents of the city of Pachuca, Hidalgo, who had a car and expressed their experiences and perceptions about this strategy. The ATLAS ti 9 software was used for data processing through open coding with categories and codes defined from the reference survey as mentioned by Dávila, G. (2006), performing inductive analyzes. The results indicate that there are perceptions related to corruption, since the measures of "healthy distance" are not respected, since the use of public transport does not allow it, as well as the control of the use of a mask. It is concluded that the experiences and perception of private car users during the implementation of the strategy was negative; Since it has caused confusion in the implementation rules and government decisions, there is no coherence on the sanitary measures of safe distance and the use of masks, both in public and private transport.
Keywords: Phenomenology; social marketing; experience; perception; COVID-19 strategy